(untitled) (Community Based Medical Journal, 2013)
Introduction: In gastric cancer surgery, gastrojejunostomy is one of the most important procedures. Anastomosis between different parts of the stomach and the intestine is a basic technical component in all gastrointestinal procedure. Backgrounds and aims: This study evaluated complications of gastrojejunostomy in gastric cancer surgery with two methods: single-layer and double-layer anastomosis. Materials and methods: This study was carried out in the department of surgery in Mymensingh Medical College Hospital from January 1, 2009 to December 31, 2012. 100 patients with carcinoma stomach who needed gastrojejunostomy were included in this study. These patients with average age of 43.22 years were divided in two groups (50 in each group); single-layer and double-layer anastomosis. In single-layer anastomosis gastrojejunostomy was performed in interrupted method with absorbable suture (2/0 vicryl). Double-layer anastomosis was carried out with continuous suture (2/0 silk, 2/0 catgut). Possible post-operative complications like anastomotic leakage, pelvic abscess, abdominal sepsis, anastomotic stenosis and wound infection were evaluated. Results: In the single-layer group, 4 patients (8%) developed anastomotic leakage, wound infection and only 2 patients (4%) developed abdominal sepsis, pelvic abscess and anastomotic bleeding. No patient developed anastomotic stricture. In double-layer group, 2 (4%) patients developed anastomotic leakage, only 1 (2%) patient had pelvic abscess, abdominal sepsis and anastomotic bleeding but wound infection in 2 (4%) patients. Conclusion: Gastrojejunostomy with single-layer hand-sewn suture technique is safe without serious complications in comparison to double-layer suture technique. More-over operation time is less and cost is less in single-layer method. DOI: http://dx.doi.org/10.3329/cbmj.v2i2.16695 Community Based Medical Journal 2013 July: Vol.02 No 02: 30-34